Autoimmune disorders and quadrivalent human papillomavirus vaccination of young female subjects. (22nd November 2013) - Grimaldi‐Bensouda, L.; Guillemot, D.; Godeau, B.; Bénichou, J.; Lebrun‐Frenay, C.; Papeix, C.; Labauge, P.; Berquin, P.; Penfornis, A.; Benhamou, P.‐Y.; Nicolino, M.; Simon, A.; et al.
Abstract Objectives The aim of this study was to investigate whether the quadrivalent human papillomavirus (HPV) vaccine Gardasil is associated with a change in the risk of autoimmune disorders (ADs) in young female subjects. Design Systematic case–control study of incident ADs associated with quadrivalent HPV vaccination in young women across France. Participants and setting A total of 113 specialised centres recruited (from December 2007 to April 2011) females aged 14–26 years with incident cases of six types of ADs: idiopathic thrombocytopenic purpura (ITP), central demyelination/multiple sclerosis (MS), Guillain–Barré syndrome, connective tissue disorders (systemic lupus erythematosus, rheumatoid arthritis/juvenile arthritis), type 1 diabetes mellitus and autoimmune thyroiditis. Control subjects matched to cases were recruited from general practice. Analysis Multivariate conditional logistic regression analysis; factors included age, geographical origin, smoking, alcohol consumption, use of oral contraceptive(s) or vaccine(s) other than Gardasil received within 24 months before the index date and personal/family history of ADs. Results Overall, 211 definite cases of ADs were matched to 875 controls. The adjusted odds ratio (OR) for any quadrivalent HPV vaccine use was 0.9 [95% confidence interval (CI) 0.5–1.5]. The individual ORs were 1.0 (95% CI 0.4–2.6) for ITP, 0.3 (95% CI 0.1–0.9) for MS, 0.8 (95% CI 0.3–2.4) for connective disorders and 1.2 (95% CI 0.4–3.6) for type 1 diabetes. No exposure to HPV vaccine was observed in cases with either Guillain–Barré syndrome or thyroiditis. Conclusions No evidence of an increase in the risk of the studied ADs was observable following vaccination with Gardasil within the time periods studied. There was insufficient statistical power to allow conclusions to be drawn regarding individual ADs.